Performance enhancement of a high-speed railway supply system with multi module converter: a laboratory prototype model for Indian railways - Venkatasupura Vemulapati; Yerram N. Vijaykumar; Nagalamadaka Visali (Institute of Advanced Engineering and Science, 2022)
The present Indian traction supply system’s complications (neutral sections of the catenary line and issues of power quality) restrict the growth of railway transportation, particularly high-speed rail networks that are fast growing globally. The neutral sections (NS) results in loss of speed, momentum and mechanical failures that are all threatening the fast and stable operation of trains and systems. In the meantime, issues with the power quality such as the negative sequence currents (NSC), the reactive power and harmonics may create problems on the three phase grid side that cannot be overlooked. To address these two issues concurrently, a new traction power supply system is designed in this paper. The proposal will also analyses the theory of operation, build the mathematical model and develop the control system for back to back converters. Small scale prototype is also made for validation of simulation results. The results shows that it can fulfil the practical requirements. The experimental results shows that the overall system is practically more appropriate for the high speed railway.